Influence of radio frequency magnetron sputtering parameters on the structure and performance of SiC films. Issue 17 (1st September 2021) - Liu, Meng; Yang, Yong; Mao, Quan; Wei, Yuquan; Li, Yajie; Ma, Ningning; Liu, Huan; Liu, Xuejian; Huang, Zhengren
Abstract: Amorphous SiC films fabricated by Radio frequency (RF) magnetron sputtering have been widely used due to their excellent properties including high strength, good hardness and outstanding abrasion resistance. However, most researches set a lower target-substrate distance, which limits its large-scale coating for practical industrial application. In this work, the distance between the target and substrate was enlarged to 120 mm, and the effective coating area was about four to ten times than other researches. Furthermore, the effects of sputtering power, deposition pressure, substrate temperature and bias voltage on the structure and performance of SiC films were also investigated. Finally, SiC films with high elasticity modulus (310.8 GPa) and hardness (35.6 GPa) are obtained by RF magnetron sputtering.